Tanggung Gugat Terhadap Maskapai Penerbangan Akibat Perlakuan Buruk Terhadap Penyandang Disabilitas - Julieta Britney Wattimena; Teng Berlianty; Theresia Nolda Agnes Narwadan (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: The treatment of persons with disabilities is regulated specifically, so as to provide equality for all people in obtaining facilities. However, in the case that happened to Ridwan Sumantri, in fact it was the opposite, Ridwan Sumantri is a person with a disability who in this case is unable to walk (paralyzed) and has to use a wheelchair wherever he is when traveling. Ridwan Sumantri as a person with a disability did not receive special treatment at all in the form of a companion escorting Ridwan as a person with a disability which should have been provided by the airport in this case Angkasa Pura and the airline in this case (LionAir airline). To find out and analyze legal protection for persons with disabilities who are discriminated against and find out and analyze liability against airlines due to discrimination for persons with disabilities. This research is included in normative legal research, namely research examining various positive legal provisions, various legal principles, legal principles and doctrines in order to answer the legal issues at hand. Ridwan Sumantri has been deemed to have fulfilled the elements of discrimination and violated the rights of passengers with disabilities on board the plane. The principle of persons with disabilities, as stipulated in Article 2 letter a of the Law on Disabilities in genera. Indeed, this interest relates to a power whose implementation is guaranteed and protected by law. Apart from that, Angkasa Puran and Lion Air Group Airlines as airline service providers should also be suspected of having violated Article 134 paragraph 1 and paragraph 2 of the Aviation Law, and Article 7 of the Consumer Protection Law concerning the obligations of business actors/service providers.